ANALISIS NILAI WAJAR SAHAM DAN PEMBENTUKAN PORTOFOLIO PADA SUB SEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuda Pranata; Samsuddin Samsuddin; Santy Mayda Batubara (Universitas Muhammadiyah Pontianak, 2018)
Purpose in this study is to find the reasonable value shares at subsector retail trade listed on the Indonesian stock, and the formation of portfolio shares at subsector retail trade with Capital Asset Pricing Model (CAPM), and analyzes the difference between intrinsic value and value of the stock market at subsector retail trade listed on the Indonesian stock. Method in this research to count intrinsic value shares whit the ways Dividend Discount Model (DDM), while the formation of portfolio use Capital Asset Pricing Model (CAPM), the result of research showed that the price of stock that is in the market is not shows a value that truth and in the results research no issuers having stock prices being in a condition of balance between intrinsic value and that the value of the market (Correctly Valued), and there is no significant difference where the benefits of natural and value of the market in companies registered on a stock.